PATRIARCHY IN FAMILY CARE- GIVING: EXPERIENCES OF FAMILIES OF CHILDREN WITH INTELLECTUAL DISABILITY IN PAKISTAN - Ahmed, Shakeel; Ali, Johar; Sanauddin, Noor (Journal of Postgraduate Medical Institute, 2016)
Objective: To know the effects of children with intellectual disability (ID) on families in Pakistan with special focus on the experiences of mothers living in nuclear and joint families. Methodology: This was qualitative study in which qualitative methods were employed for this study. Data was collected from parents and family mem-bers of children with intellectually disability. Participants from the diverse socio-economic features were selected from the three rehabilitation centres for children with intellectual and physical disability in Peshawar and Haripur districts of Khyber Pakhtunkhwa province. A total of 58 respondents were in-terviewed including 30 in-depth individual interviews (IDIs) with parents hav -ing children with ID and 4 Focus Group Discussions (FGDs) with a total of 28 parents (7 participants in each FGD). Both mothers and fathers participated in this study for ensuring equal gender ratio. Results: Women in the families were suffering more as compare to men due to socially assigned role of primary care of the children. Women were facing social exclusion, stress/ fatigue due to role strain, rejection in the form of family breakdown and work-family conflict due to gender imbalance in role performances. Moreover, families were also prone to displacements and so-cial hazards like beggary, child labour and drop out of normal female children from schools due poor institutional role in child support and rehabilitation. Conclusion: Patriarchy promotes uneven distribution of roles for men and women in the families having children with ID which causes more agonies for mothers and other female members of the house as compared to male members of the family.